Provincial and Territorial Government Contributions to the Development of Francophone Minority Communities: Assessment and Projections - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Canadian Institute for Research on LInguistic Minorities, 2007)
For more than forty years, the governments of the nine provinces and three northern territories that are majority Anglophone have been striving to promote the language and culture of their Francophone minority and thereby contribute to its development. Indeed, despite the importance of the federal government contribution, sectors such as education, health, and social and municipal services that are areas of exclusive provincial and territorial jurisdiction contribute to the vitality of Francophone communities. The lack of literature on provincial and territorial action in the area of official languages might lead one to think that such action is rare, or even non-existent, or that it is aimed at inhibiting the development of Francophone communities. It is nothing of the sort. Compilation and analysis of provincial and territorial actions in the area of official languages were thus required. It was necessary first to identify the nature of these actions and compile a list of them, and second to assess them critically. We then proposed a few immediate and long-term projections. The research covered nine sectors of activity: 1) public communications and services, 2) early childhood development, 3) health and well-being, 4) justice, 5) arts and culture, 6) economic development, 7) target groups (youth, seniors, and women), 8) immigration and 9) municipalities. The section on Health and Well-being discuss 6 themes: a) Legislation and Case Law; b) Policy; c) Programs and Services; d) Publications and Other Documents; e) Financial Support and Institutionalization; f) Training.
Research report prepared on behalf of the Ministerial Conference on the Canadian Francophonie

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire - MacLean, Patsy; Robinson, Constance; Lewis, Kay; HRA, firme d’experts-conseils (Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français, 2007)
fs-ref-orig: MacLean, P., Robinson, C. et Lewis, K. (2007). Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire. Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français. fs-code-orig: MacLean-2007

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)
https://pmc.ncbi.nlm.nih.gov/articles/PMC2231483/